(untitled) (Eurasian Research Bulletin, 2023)
In this article, cases where agionymic lexemes are used in the realization of poetic expression and aesthetic evaluation are analyzed. Each prophet’s name has expressed a certain concept as a symbol in our classical literature. Poets appropriately used these symbols to express their subjective assessment and created beautiful images